(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
From the perspective of enterprise management, tax optimization begins with robust internal accounting, the establishment of tax planning as a systematic function, and the implementation of effective internal controls. Enterprises must remain continuously updated with changes in tax legislation, and must invest in professional expertise to ensure compliance while leveraging available deductions and credits. Detailed attention to the correct categorization of expenses and revenues, appropriate inventory valuation, and the substantiation of non-taxable income streams can lead to substantial tax efficiencies.